Letter from James Curtis Booth to Joseph B. Townsend - Booth, James Curtis (1878)
James Curtis Booth (1810-1888) writes to Joseph B. Townsend (1821-1896) a Philadelphian lawyer, to thank him for his loan of $500. Includes two notes from Booth concerned with the loan.
Keywords: Booth, James Curtis, 1810-1888; Loans